2008
DOI: 10.1063/1.2829591
|View full text |Cite
|
Sign up to set email alerts
|

Visual phenomena of surface plasmon polaritons at the dielectric-plasma interface

Abstract: Some interesting experiment phenomena of light patterns that appear in microwave plasma have been investigated. The wavelength of surface plasmon polaritons (SPPs) at the dielectric-plasma interface as the functions of incident wave frequency and plasma density has been calculated. The comparison of the experiment results with the calculating results has been carried out. By experimentally and theoretically analyzing, the phenomena are considered to be caused by the surface wave of SPPs at the interface betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…Therefore, a possible way to control the discharge effectively is to utilize the plasmadielectric resonator, i.e., to apply the periodic slot antennas as the microwave energy excitation. [7][8][9][10][11][12][13][14] However, the SWP sources designed with the special wave-mode conversion device are not clearly described at the discharge pressure of about 100 Pa. Furthermore, the effect of wave-mode conversion device on the production of large-area uniform stable overdense plasmas has not been proposed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, a possible way to control the discharge effectively is to utilize the plasmadielectric resonator, i.e., to apply the periodic slot antennas as the microwave energy excitation. [7][8][9][10][11][12][13][14] However, the SWP sources designed with the special wave-mode conversion device are not clearly described at the discharge pressure of about 100 Pa. Furthermore, the effect of wave-mode conversion device on the production of large-area uniform stable overdense plasmas has not been proposed.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, the development and application researches of the large-scale overdense SWP have attracted the unprecedented attention and the current study focus on the spatial uniformity and the temporal stability in large area. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] To address the above concerns, a lot of planar-type SWP sources have been optimized. As for these sources, the uniformity of plasma below the dielectric slab is one of the most important factors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Also peoples have used slot antennas for launching of microwave [4][5][6][7][8] for higher densities. In slot antenna configuration, plasma lengths are broadened with decrease in gas pressures.…”
Section: Introductionmentioning
confidence: 99%
“…9 In dielectric-bounded SWP sources, more than 200 W microwave power is injected. [1][2][3][4][5][6][7][8][9][10][11][12] In MVP sources, microwave plasmas are produced along a dielectric-free metal antenna and the surface waves propagate along the plasma-sheath interfaces. In 2005, Kousaka et al 13 at Nagoya University reported a new SWP source which can generate over-dense plasma along the surface of a negative biased metal rod, called metal-antenna surface wave excited plasma (MASWP).…”
Section: Introductionmentioning
confidence: 99%
“…In general, dielectric-bounded SWP sources employ dielectrics such as a quartz plate [3][4]6] or a quartz tube [7][8][9][10], along which high density plasmas are sustained by electromagnetic waves travelling along plasma-dielectric surface boundaries [10][11][12][13][14][15][16][17][18][19][20][21]. Dielectric-bounded SWP sources have never been used for sputtering, because they are not generated near and along a metal target as in conventional magnetron sputtering sources [1].…”
Section: Introductionmentioning
confidence: 99%